2021
DOI: 10.3390/ijerph18147407
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Face Masks on the Use of Contact Lenses

Abstract: Background: The COVID-19 epidemic is largely controlled by the use of face masks. The use of a face mask has been indicated as a strong cause of dry eye, although it is not yet described in the literature. This study aims to compare the impact of the use of masks on the visual quality of patients. The symptoms in the human eye intensified during the pandemic versus the symptoms before the pandemic, in a Portuguese population. Methods: A fifteen-question questionnaire was conducted to find out what changes occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Most individuals were simply leaving home less often, which minimised the need to wear contact lenses. The findings are generally consistent with previous reports undertaken earlier in the pandemic, in the UK, Ireland, Spain, Portugal, Greece and Jordan where a decline in social interactions and activities/leaving home were also cited as common reasons for decreasing lens wear [16] , [21] , [22] , [23] , [24] , [25] , [20] . Secondary concerns, however, differ both within the cohort investigated and more widely.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most individuals were simply leaving home less often, which minimised the need to wear contact lenses. The findings are generally consistent with previous reports undertaken earlier in the pandemic, in the UK, Ireland, Spain, Portugal, Greece and Jordan where a decline in social interactions and activities/leaving home were also cited as common reasons for decreasing lens wear [16] , [21] , [22] , [23] , [24] , [25] , [20] . Secondary concerns, however, differ both within the cohort investigated and more widely.…”
Section: Discussionsupporting
confidence: 92%
“…Further demand for services could arise from patients seeking help for symptoms experienced during the pandemic, e.g., an exacerbation of digital eye strain or dry eye syndromes such as MADE [23] . Patients who continue to harbour concerns about hygiene may be tempted to avoid regular replacement lenses in favour of daily disposables [25] , and those frustrated by mask induced fogging of spectacles [30] ) could perhaps be more motivated to embrace contact lenses.…”
Section: The Futurementioning
confidence: 99%
“…As described in Martinez-Perez et al [29], the existence of non-sealed areas between the mask and the face can generate health problems, such as dry eyes. It was found that most people presented symptoms of visual diseases caused by the continuous mask usage.…”
Section: Introductionmentioning
confidence: 99%
“…With the onset of the COVID-19 Pandemic, the new norms of living style have changed. Mask wear or proper protective gear has become mandatory at all working stations [8]. The mode of education & working patterns changed from online to hybrid practices where students & other professions were involved in using digital devices for online working patterns and an offline mode.…”
Section: Introductionmentioning
confidence: 99%